2021
DOI: 10.1097/yic.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and safety of cariprazine in schizophrenia patients with negative symptoms and insufficient effectiveness of previous antipsychotic therapy: an observational study

Abstract: The aim of the study was to examine the effectiveness and safety of cariprazine in routine psychiatric settings on schizophrenia patients with negative symptoms who have been treated with antipsychotics previously but without sufficient success. This was an open-label, flexible-dose, 16-week, observational study in Latvia. The primary outcome measure was an array of anamnesisbased clinical questions on schizophrenia symptoms rated on a seven-point scale. Other outcome measurements were the clinical global impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 48 publications
4
33
0
Order By: Relevance
“…Similar results were acquired in the Latvian observational study as well, where about 40% of patients had at least one TEAE; most commonly akathisia (13%), anxiety (10%) or parkinsonism (6%) [12]. Nonetheless, the physicians overall impression about tolerability was highly positive: 45% were very satisfied and 39% were satisfied with cariprazine [12].…”
supporting
confidence: 78%
See 3 more Smart Citations
“…Similar results were acquired in the Latvian observational study as well, where about 40% of patients had at least one TEAE; most commonly akathisia (13%), anxiety (10%) or parkinsonism (6%) [12]. Nonetheless, the physicians overall impression about tolerability was highly positive: 45% were very satisfied and 39% were satisfied with cariprazine [12].…”
supporting
confidence: 78%
“…In addition, a real-world study has also confirmed the results of the Nemeth et al trial recently [10]. A 16-week, open-label observation study conducted in Latvia found support for the notion that cariprazine has the ability to improve negative symptoms in schizophrenia patients with predominant negative symptoms who have been treated with antipsychotics previously but without sufficient response [12]. In this trial significant improvement in the five domains of negative symptoms were detected from week 2 onwards [12].…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Cariprazine was also found to be uniquely effective in treating primary negative symptoms of schizophrenia, due to its predominant preference for D3 receptors, as well as its considerable affinity for 5-HT 1A receptors (33)(34)(35)(36)(37). In a randomized, double-blind multicenter study which compared the efficacy of cariprazine and risperidone in patients with schizophrenia with predominantly negative symptoms, cariprazine in the mean dose of 4.2 mg/d showed a superiority over risperidone (mean dose 3.8 mg/d) at Week 14, which was continued until Week 26 (end of trial) (33).…”
Section: Cariprazine Efficacy Across the Wide Range Of Symptoms Of Schizophreniamentioning
confidence: 99%